Preoperative high-precision three-dimensional reconstruction in laparoscopic splenectomy for supramassive splenomegaly: a case report and literature review - Huang, Cheng; Gao, Zhichao; Zhang, Yuhang; Ge, Lida (Frontiers in Medicine, 2025)
BackgroundMassive splenomegaly is considered to pose a high risk for laparoscopic splenectomy (LS). We report a case of supramassive splenomegaly wherein the patient successfully underwent LS guided by preoperative three-dimensional (3D) reconstruction.Case presentationA 35-year-old female had a history of autoimmune hepatitis spanning 4 years, accompanied by progressive splenomegaly. Her spleen had grown to a size of 27.3 cm in diameter, and a consistent decline in her blood cell counts had been noted over the same period. Considering the significant enlargement of the spleen and the technical challenges associated with LS in such instances, a preoperative 3D reconstruction was performed. This 3D model accurately delineated the splenic artery and depicted the positional relationships between the enlarged spleen and nearby organs, thus supporting detailed preoperative planning. Following the surgical route determined in the preoperative planning, 3D assistance enabled the safe ligation of the splenic artery and meticulous separation of the spleen from adjacent tissues. The patient’s postoperative recovery was smooth and free from complications.ConclusionMeticulous preoperative 3D planning may help overcome technical difficulties and enable successful LS even in patients with supramassive splenomegaly.